PERANCANGAN STRUKTUR DERMAGA CURAH KERING TIPE DECK ON PILE DI PELABUHAN BELAWAN, KOTA MEDAN, PROVINSI SUMATERA UTARA - Sebastian Panjaitan, Kevin
Indonesia is a maritime country, with a sea area much larger than the land area. In its development, adequate transportation access is needed to connect every region in Indonesia with other regions. Belawan Port is one of the leading access points on the western side of Indonesia, which is a connecting door to help the development of the surrounding area. In the case study of the Final Project on Design of Dry Bulk Dock Structure with Deck on Pile Type in Belawan Port, Medan City, North Sumatra Province, will discuss about the design of the dock structure based on the design criteria used as structural planning requirements by considering the environmental conditions at the study location. This final project covers the dimensions of the dock, structural modeling, design of structural elements reinforcement and calculation of soil bearing capacity. Structural modeling is carried out using SAP2000 software to determine the quality of the design structure of the plan against the working loads. The results of this modeling are UCR (Unity Check Ratio) values, structural deflection, forces in beams and slabs and the value of the bearing reaction. The design reference used is the UCR value where a reliable and optimal structure has a value in the range of 0.7 to 1.0. Examination of the deflection value is carried out as an aspect of the feasibility of the structure with the deflection value obtained must be between the permissible limits. The forces in the dock structural elements obtained from the modeling results are used as the basis for reinforcing the dock structural elements. Reinforcement ratio examination is carried out to determine the optimal cross-sectional area. The results of the final project include the design of the dock which includes the dimensions of the structure and the dimensions of the structural elements, the details of reinforcement based on the working internal forces, as well as the depth required in the pile that is able to withstand the reaction of the structure based on geotechnical data